EDUKASI PEMBERIAN SARI KACANG HIJAU (VIGNA RADIATE) SEBAGAI UPAYA PENINGKATAN PRODUKSI ASI PADA IBU NIFAS - Naimah Nasution; Kristin Natalia; Septa Dwi Insani; Juliana Sion Sihombing (INSTITUT KESEHATAN DELI HUSADA, 2023)
Exclusive breastfeeding refers to the practice of providing breast milk solely to infants aged 0-6 months without introducing any additional solid foods or liquids such as formula, fruit juice, honey, or tea. The objective of this study is to assess the impact of administering green bean juice (Vigna Radiate) on enhancing postpartum breast milk production among mothers receiving care at the Yeni Clinic in the Tinggi Raja District, Asahan Regency, in the year 2022. This research follows a quantitative approach and employs a quasi-experimental design known as the